(untitled) (Global Journal of Science Frontier Research, 2025)
This short communication presents an original educational and cultural initiative organized in Lavras Brazil to celebrate the winter solstice through science art and local traditions Inspired by astronomical knowledge and the rich context of Festa Junina the event invites people to dress their shadow at true solar noon the moment when the Sun reaches its highest point in the sky and casts the shortest shadow In Lavras during the solstice the Sun reaches an altitude of about 45 above the horizon causing a person s shadow to match their height Participants place a change of clothes or traditional attire over their shadow and photograph the scene posting it with the hash tag solsticiolavras This initiative creatively connects everyday experience with astronomical concepts and pays homage to ancestral understandings of the cosmos